sedInterFoam 1.0: a three-phase numerical model for sediment transport applications with free surfaces - A. Mathieu; Y. Kim; T.-J. Hsu; C. Bonamy; J. Chauchat (Geoscientific Model Development)
In this paper, an Eulerian two-phase flow model, sedFoam, is extended to include an air phase together with its water and sediment phases. The numerical model called sedInterFoam is implemented using the open-source library OpenFOAM. sedInterFoam includes the previous features of sedFoam for sediment transport modeling and also solves the air–water interface using the volume-of-fluid method coupled with the waves2Foam toolbox for free-surface wave generation and absorption. Using sedInterFoam, four test cases are successfully reproduced to validate the free-surface evolution algorithm's implementation, mass conservation of sediment and fluid phases, and predictive capabilities and to demonstrate its potential in modeling a broader range of coastal applications with sediment transport dominated by surface waves.